BRIEF ACCOUNT OF SASAK SYNTACTIC STRUCTURE AS USED IN MERIAQ MERIKU DIALECT AT BANYU URIP VILLAGE IN 2019/2020 - Masyudi Masyudi (Lembaga Penelitian dan Pendidikan Mandala, 2019)
The research is entitled “BRIEF ACCOUNT OF SASAK SYNTACTIC STRUCTURE AS USED IN MERIAQ MERIKU DIALECT AT BANYU URIP VILLAGE IN 2019/2020” this research is aimed find, the daily used by the society of Banyu Uripvillage, the method used is descriptive method and the instrument, population and sample the writer get from the prominent person on the village by interviewing them using tape recorder and the result is the writer is able to write this thesis. It is also essential to know that syntax is also a subject that must be profoundly studied, besides morphology and semantic, this subject is the rules to build sentences, therefore, there should have a lot of vocabulary (idioms) and a lot of practice to do.We all have already been familiar with the student who write an English sentence or paragraph in much impressed by Indonesia sentence or paragraph as in Indonesia language is similar in structure to English language and definitely it sound, stilted. From now on, we know that the new student are not able to master. The English sentence structure and for these reasons, the writer tries to describe the sasak syntactic structure of MERIAQ MERIKU in simple sentence of English.